The Role of 'Persistent Resilience' within Everyday Life and Polity: Households Coping with Marginality within the 'Big Society'. (March 2015) - Andres, Lauren; Round, John
As Europe's current economic crisis continues many households are developing new coping strategies in response to the pressures of everyday life. This paper explores such practices within Birmingham's Castle Vale housing estate, drawing on the increasing engagement within the social sciences with notions of resilience. This concept, originating from engineering, psychology, and disaster management, is increasingly used in urban and economic geography, and is becoming influential on state policy. This paper furthers its current usages by proposing the concept of 'persistent resilience', whereby households, and their networks, develop responses not just to 'shocks', but also to more long-term processes, such as the changing nature of employment and/or responses to constantly altering state policies. This form of resilience has significant policy relevance, as it can be seen, albeit under different names, at the heart of the British government's 'Big Society' project, within which communities are to be empowered to steer their development while 'big government' withdraws. This paper argues, however, that there is an inherent tension within such assumptions of community-led development, as they do not consider the spaces in which it takes place. As the paper demonstrates, 'persistent resilience' is often formed in the semiformal/informal spaces of everyday life, which, in many cases, will be destroyed by cuts to government funding to communities. Thus, the paper calls for a more nuanced, everyday understanding of resilience and the spaces within which it is formed and transmitted.